A Conceptual Paper on The Link Between Homeownership, Subjective Well-being, and Wealth Concepts - Mulyadi, -; Nur Zaimah, Ubaidillah (2022)
The study of homeownership impacts on household wealth and economic development has commonly used the concept of wealth, which is limited to monetary indicators. Cultural perceptions and subjective well-being (SWB) have not been considered in determining the concept of household wealth to achieve the goals of modern economic development. This paper sees a relationship between cultural perceptions, SWB, and the concept of household wealth. The new paradigm is explained by incorporating cultural perceptions and SWB that broaden the meaning of household wealth. As a consequence of applying this new paradigm, the concept of household wealth used to analyze the impact of homeownership will vary. The difference is determined by the cultural perceptions that grow in the selected object of the study.